Frontispiece: Lanthanide Tetrazolate Complexes Combining Single-Molecule Magnet and Luminescence Properties: The Effect of the Replacement of Tetrazolate n3 by ?-Diketonate Ligands on the Anisotropy Energy Barrier - Aravena-Ponce, D; Aravena-Ponce, D (Wiley-VCH Verlag, 2016)
Sin Resumen Disponible